2015
DOI: 10.17116/hirurgia20151272-79
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate after D3-lymphadenectomy for right-sided colic cancer: case-match study

Abstract: D3-lymphadenectomy and mesocolectomy for right-sided colon cancer stage I-III without adjuvant chemotherapy provides significantly better overall and cancer-related 5-year survival compared with conventional right-sided hemicolectomy. Thus, D3-lymphadenectomy and mesocolectomy in compliance with «no-touch» principle for right-sided colon cancer is reproducible and effective in Russian conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Patients with CRC who received D3/D2 lymphadenectomy have superior OS. [30][31][32] To avoid this limitation, we only enrolled patients with at least twelve harvested lymph nodes. Second, detailed information about chemotherapy was not recorded in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CRC who received D3/D2 lymphadenectomy have superior OS. [30][31][32] To avoid this limitation, we only enrolled patients with at least twelve harvested lymph nodes. Second, detailed information about chemotherapy was not recorded in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of both techniques is to enhance overall and disease-free survival. Numerous non-randomized controlled trials have demonstrated the superiority of D3 lymph node dissection over D2 in terms of overall and disease-free survival [ 9 12 ]. Other authors have shown comparable long-term results [ 13 , 14 ].…”
Section: Background and Rationalementioning
confidence: 99%
“…В данном обзоре предполагается, что лимфаденэктомия в объеме D3 превосходит таковую в объеме D2, улучшая отдаленные результаты в отношении кровопотери, количества полученных ЛУ и 3-и 5-летней общей и безрецидивной выживаемости [62]. Схожие результаты наблюдались при анализе других исследований [63,64]. При рассмотрении вопроса о выборе объема лимфаденэктомии при правосторонней локализации рака следует упомянуть исследование Y. Kanemitsu и соавт.…”
Section: стандарты лимфаденэктомииunclassified